Hospital librarians as publishers: expanding our role. - Samsundar, Devica R.; Figueredo, Carrie (Journal of the Medical Library Association, 2018)
Librarians at Baptist Health South Florida (BHSF) launched the first peer-reviewed journal from BHSF, Nursing & Health Sciences Research Journal (NHSRJ). This article discusses how it was developed, the role of the librarians, and future goals of the journal.